VERIFIKASI METODE UJI TOTAL REDUCING SUGAR ICUMSA GS4/3-7 (2011) - Lestari, Puji Pangestu; Ma'sum, Zuhdi (eUREKA : Jurnal Penelitian Teknik Sipil dan Teknik Kimia, 2017)
Based on ISO / IEC 17025: 2008 Clause 5.4 states that an accredited laboratory should select the appropriate method, already published in the international standard, regional or national, or reputable technical organizations or from the text or the relevant scientific journals. Laboratories should ensure that can operate standard methods before introducing the tests is to verify the standard method. As an accredited laboratory, the LP-P3GI need to perform verification testing methods to determine whether the total reducing sugar method ICUMSA GS4 / 3-7 (2011) can be applied or applied in LP-P3GI the results are valid and reliable, so that the results of the verification the method can be used as a quality assurance testing. In the verification method, a performance that will be tested is the precision (austerity). Precision is the degree of accuracy the value of some of the results of repeat testing. Precision test can be done by performing intra repeatability and reproducibility. The results of precision test repeatability value CV = 0.75% < 2/3 CV Horwitz = 1.44%, while the intra-precision test reproducibility CV = 1.11%